BCPT: Participant Update - K. Smigel (JNCI Journal of the National Cancer Institute, 1994)
Genetic hypertrophic and dilated cardiomyopathies (HCM and DCM, respectively) are characterised by structural and functional abnormalities that can lead to heart failure. However, current therapies mainly reduce symptoms. Patient-derived human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes provide a valuable platform to study genotype-specific pathophysiology and pharmacology. We subjected hiPSC-cardiomyocytes from healthy individuals and from patients carrying pathogenic MYBPC3 (HCM) or LMNA (DCM) mutations to cyclic mechanical stretch, with or without the GATA4-targeted anti-hypertrophic compound 3i-1262, and assessed hypertrophy-associated, mechanosensitive and metabolism-related genes by qPCR, and hypertrophy-related proteins by Western blotting. Compared to control, HCM cardiomyocytes displayed higher basal expression of NPPB and MYH7, whereas DCM cardiomyocytes exhibited lower basal expression of NPPB and NPPA. Mechanical stretching induced NPPB and MYH7 upregulation in control cardiomyocytes, delayed MYH7 upregulation in HCM cardiomyocytes and NPPA downregulation in DCM cardiomyocytes. Other mechanosensitive genes, such as GAL, CSRP3 and SLC16A9, also exhibited genotype- and time-dependent regulation. In control cardiomyocytes, 3i-1262 produced limited modulation of stretch-induced gene expression but showed little or no effect in patient-derived cardiomyocytes. These findings demonstrate that cardiomyopathy mutations influence gene and protein expression, responses to mechanical stretch and 3i-1262, underscoring the value of patient-derived hiPSC-cardiomyocytes in disease modelling and drug discovery.